2020
DOI: 10.3389/fmars.2019.00788
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Genome-Wide Methylation and Gene Expression in Response to Future pCO2 Extremes in the Antarctic Pteropod Limacina helicina antarctica

Abstract: Epigenetic processes such as variation in DNA methylation may promote phenotypic plasticity and the rapid acclimatization of species to environmental change. The extent to which an organism can mount an epigenetic response to current and future climate extremes may influence its capacity to acclimatize or adapt to global change on ecological rather than evolutionary time scales. The thecosome pteropod Limacina helicina antarctica is an abundant macrozooplankton endemic to the Southern Ocean and is considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 119 publications
3
29
0
Order By: Relevance
“…In the present study, OA was associated with a genome-wide decrease in methylation (hypomethylation), similar to the response observed in pteropods (Bogan et al, 2020) , but opposite the response observed in corals (Putnam et al, 2016;Liew et al, 2018) . Over time, an increase in methylation (hypermethylation) was observed, also consistent with the DNA methylation response observed in pteropods (Bogan et al, 2020) . Unlike for the pteropods, the same degree of hypermethylation through time was observed in both the control and high OA treatments (i.e., no interaction between treatment and time).…”
Section: Dna Methylationsupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, OA was associated with a genome-wide decrease in methylation (hypomethylation), similar to the response observed in pteropods (Bogan et al, 2020) , but opposite the response observed in corals (Putnam et al, 2016;Liew et al, 2018) . Over time, an increase in methylation (hypermethylation) was observed, also consistent with the DNA methylation response observed in pteropods (Bogan et al, 2020) . Unlike for the pteropods, the same degree of hypermethylation through time was observed in both the control and high OA treatments (i.e., no interaction between treatment and time).…”
Section: Dna Methylationsupporting
confidence: 82%
“…This genome-wide DNA methylation response to OA has been found in several other species of marine calcifiers, including corals, pteropods, and in the gonadal tissue of C. virginica (Putnam et al, 2016;Liew et al, 2018;Bogan et al, 2020;Venkataraman et al, 2020) . In the present study, OA was associated with a genome-wide decrease in methylation (hypomethylation), similar to the response observed in pteropods (Bogan et al, 2020) , but opposite the response observed in corals (Putnam et al, 2016;Liew et al, 2018) . Over time, an increase in methylation (hypermethylation) was observed, also consistent with the DNA methylation response observed in pteropods (Bogan et al, 2020) .…”
Section: Dna Methylationmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, we also hypothesized that OA-induced shifts in the transcriptome of C. virginica would correspond to shifts in the methylome. This was based on growing evidence in the DNA methylation literature indicating that DNA methylation is linked with gene regulation (Zilberman et al, 2007;Zemach et al, 2010;Gavery and Roberts, 2013;Olson and Roberts, 2014;Dixon et al, 2018;Zhang et al, 2020), is induced by OA and other environmental stressors (Putnam et al, 2016;Dixon et al, 2018;Bogan et al, 2020), and corresponds with calcification response to OA in marine invertebrates (Liew et al, 2018).…”
Section: Stress and Metabolic Responsesmentioning
confidence: 99%
“…At the transcriptomic level, this cost can manifest as shifts in the expression of both calcification and metabolic genes over time (Li et al, 2016), suggesting that certain acclimatization responses may be unsustainable during extended exposure to OA. The precise mechanisms that mediate these changes in gene expression remain underexplored, but recent studies indicate that DNA methylation, an epigenetic modification, may be an important regulator of these responses (Liew et al, 2018;Bogan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%